Understanding LTP in pain pathways - Sandkühler Jürgen (SAGE Publishing, 2007)
Abstract Long-term potentiation (LTP) at synapses of nociceptive nerve fibres is a proposed cellular mechanism underlying some forms of hyperalgesia. In this review fundamental properties of LTP in nociceptive pathways are described. The following topics are specifically addressed: A concise definition of LTP is given and a differentiation is made between LTP and "central sensitisation". How to (and how not to) measure and how to induce LTP in pain pathways is specified. The signal transduction pathways leading to LTP at C-fibre synapses are highlighted and means of how to pre-empt and how to reverse LTP are delineated. The potential functional roles of LTP are evaluated at the cellular level and at the behavioural level in experimental animals. Finally, the impact of LTP on the perception of pain in human subjects is discussed.